TOURISM COOPERATION AND PEACE - AN EXAMPLE FROM THE DIVIDED NATION OF KOREA - YOUNG - SUN SHIN (ASEAN Journal on Hospitality and Tourism, 2005)
At the end of 1996, international tourist arrivals reached 600 million, generating US $423 billion. By the year 2020 tourist arrivals will reach to 1.6 million (WTO, 1997). Despite the strength of global tourist demand, many destinations especially in the third world, are facing fluctuations in tourist arrivals, due to unsafe political conditions. Richter (1992, p.36) points at the fifth critical element 'S'-security, in addition to four favourable 'S's' (sun,sea, sand, sax) which are often seen as the core of developing a nation's tourist appeal. This paper addresses a number of key issues related to tourism cooperation and peace, using the case study of the divided nation between South Korea and North Korea. The research and analysis of this case includes both theory and facts. The theoretical concepts are of two kinds: theories on division and political boundary and theories on peace and tourism. The purpose of this paper is to expose the current economic condition of the tourism industry in South and North Korea, and the suggested options for tourism cooperation.